1994
DOI: 10.1002/hlca.19940770619
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Formation of Ternary Copper(II) Complexes of (S)‐amino‐acid amides and (R)‐ or (S)‐amino acids in aqueous solution

Abstract: Formation constants of ternary complexes of Cu" with (S)-amino-acid amides (phenylalaninamide, proiinamide, and tryptophanamide) and (R)-or (S)-amino acids (valine, phenylalanine, proline, and tryptophan) were determined potentiometrically at 25" and I = 0 . 1~ (KC1). Significant stereoselectivity was found for the systems (S)-tryptophanamide/proline, (S)-prolinamide/tryptophan, and (S)-phenylalaninamide/proline, the diastereoisomeric complexes with 'homochiral' ( S S ) being more stable than with 'heterochira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…The potentiometric apparatus for the automatic data acquisition was described previously. [32] A Hamilton combined glass electrode (P/N 238 000) was employed and was calibrated in terms of [H + ] concentration by titrating HCl solutions with KOH (pH = Àlog [H + ]), as reported previously. [32] The pK w value was 13.77(1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The potentiometric apparatus for the automatic data acquisition was described previously. [32] A Hamilton combined glass electrode (P/N 238 000) was employed and was calibrated in terms of [H + ] concentration by titrating HCl solutions with KOH (pH = Àlog [H + ]), as reported previously. [32] The pK w value was 13.77(1).…”
mentioning
confidence: 99%
“…[32] A Hamilton combined glass electrode (P/N 238 000) was employed and was calibrated in terms of [H + ] concentration by titrating HCl solutions with KOH (pH = Àlog [H + ]), as reported previously. [32] The pK w value was 13.77(1). The protonation constants of GABAha were determined by alkalimetric titration of four samples (4.7-7.1 10 À3 m).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…0.2 ) were prepared by diluting concentrated Merck Titrisol ampoules and standardized with the reported procedures. [22] The titrant solution of HOTf (ca. 15 ϫ 10 -3 ) was prepared by dissolving pure triflic acid (15 µL) in CH 2 Cl 2 (10 mL) with the addition of reagent grade methanol (150 µL).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we have shown that with bis(amino acid amidato)copper(II) complexes added to the eluent, ligand exchange is actually occurring in the chromatographic system, leading to formation of the ternary diastereomeric complexes and displacement of one ligand. However, we have also shown that the equilibria of ligand exchange occurring in the mobile phase are not sufficient to account for the o v e d discrimination process, 23 and that a series of partition equilibria of the different species occurring between the aqueous and the organic phase is involved. In order to favour the discrimination process occurring on the stationary phase, we modified the chiral selector slightly by introducing lipophilic chains in the amino acid amides so that they could be dynamically adsorbed on an octadecyl silica gel column.…”
Section: Introductionmentioning
confidence: 97%